Peningkatan Parenting Self Efficacy pada Ibu Pasca Seksio Sesaria melalui Konseling - Diah Astutiningrum; ELsi Dwi Hapsari; Purwanta Purwanta (Universitas Airlangga, 2016)
Introduction: Parenting Self Efficacy (PSE) is the conviction of parents for their ability to manage and perform tasks related to parenting. Pain after caesarean childbirth can reduce the ability and lower confidence in caring for the babies. Counseling on postpartum mother is an effort to increase confidence in caring for the baby. This study was aimed to test the effect of counseling given to mothers after caesarean section to increase PSE.Methods: The study used a quasi experimental with pre-test and post-test with control group. Number of research subjects were 66 divided into an experimental group and control group. Subject who pass the inclusion criteria, given the questionnaire and conducted pre-test with parenting selfefficacy scale (PSEs), given counseling and provide booklets in the experimental group, while the control group only given booklets. Measurements were made with instruments of parenting self-efficacy scale (PSEs). The statistical test used was paired t-test and independent sample t-test.Results: Increased PSE significant score after the intervention in the experimental group and the control group (6.19 ± 0.93 vs 7.54 ± 0.71, P = 0.001; 5.56 ± 0.85 vs 5.87 ± 0 , 68, P = 0.001). Changes in scores after the intervention were significantly higher in the experimental group than the control group (1.35 ± 0.58 vs 0.31 ± 0.26, p = 0.000).Conclusion: Counseling by using booklets effect on parenting self-efficacy in women after caesarean section.